Ethnic and sex differences in the longitudinal association between heart rate variability and blood pressure. (4th May 2021) - Hill, LaBarron K.; Thayer, Julian F.; Williams, DeWayne P.; Halbert, James D.; Hao, Guang; Robinson, Vincent; Harshfield, Gregory; Kapuku, Gaston
Abstract: Purpose: Elevated blood pressure is a risk factor for increased cardiovascular morbidity and mortality. Decreased vagally-mediated heart rate variability has previously been prospectively linked with increased blood pressure; however, to date, no such prospective data exist regarding this relationship among Blacks. Materials and methods: We examined this association in 387 normotensive young adults (mean age, 23 years, 52% female, 54% Black) who participated in two laboratory evaluations spanning approximately six years. Blood pressure was measured at both timepoints with a non-invasive oscillometric device and heart rate variability was assessed via bio-impedance. Results: In the total sample, heart rate variability significantly predicted systolic ( p = .022) and diastolic ( p < .001) blood pressure increases six years into the future. However, this pattern varied as a function of ethnicity and sex with the effect of heart rate variability on Time 2 systolic blood pressure only significant among White males ( p = .007). Heart rate variability was also predictive of Time 2 diastolic blood pressure in White males ( p  = .038) as well as among both White ( p  = .032) and Black ( p  = .015) females, but was not related to blood pressure among Black males. Conclusion: We report for the first time significant ethnic and sex differences in the prospective relationship between heart rate variability and blood pressure change. These findings may give clues as to the underlying mechanisms that are involved in the well-known health disparities in blood pressure and hypertension-related cardiovascular diseases.